Drug Susceptibility Patterns of Uropathogens Isolates from Suspected UTI Patients Attending Zawia Medical Center, Libya - Nadya Elarusy,; Nasreen Alarosi,; Amnah Mohammed,; Ibtisam Khapoli, (AlQalam Journal of Medical and Applied Sciences, 2025)
Urinary tract infections (UTIs) are among the common reasons for seeking medical attention in the community. Understanding the characteristics of uropathogens and their antimicrobial susceptibility pattern in a particular setting can provide evidence for the appropriate management of cases. Therefore, the aim of current study is to determine the prevalence of uropathogens associated with UTIs, and estimated their sensitivity profile among different age groups in Zawia Teaching hospital. A retrospective study was conducted from 1stJanuary, 2022 to December 31th 2022 in Zawia Teaching hospital. Patients of all ages and both sexes were included in the study. Laboratory reports of patients with a positive urine culture (≥105 CFU/mL) and antibiotic susceptibility testing were included in the study. Out of 1966 samples, 506 cases were a positive culture. Of whom, 378(74.70%) were female and 128(25.30%) were male. The majority of positive cultures was recorded in the adolescent age group of 11–20 years (38.14%). Regarding the isolated uropathogens, the E. coli was the dominant bacterial isolate with 261 (51.58%) of the total samples. On the other hand, the gram-positive bacteria (Staphylococcus spp) recorded the lowest abundant uropathogen with 15 (2.96%) of the total examined samples. The Pseudomonas spp was the most resistant bacterium. For all Gram-negative bacteria were highly resistant to Augmentin, whereas Gram-positive bacteria were highly resistant to Penicillin. The obtained results emphasized the emergence of highly resistant bacteria to most of the tested antimicrobials and propose the need for physicians to change their treatment pattern depending on antimicrobial susceptibility results. تعد التهابات المسالك البولية من الأسباب الشائعة لطلب الرعاية الطبية في المجتمع. إن فهم خصائص مسببات الأمراض البولية ونمط حساسيتها للمضادات الحيوية في بيئة معينة يمكن أن يوفر دليلاً على الإدارة المناسبة للحالات. لذلك، فإن الهدف من الدراسة الحالية هو تحديد انتشار مسببات الأمراض البولية المرتبطة بالتهابات المسالك البولية، وتقدير ملف حساسيتها بين الفئات العمرية المختلفة في مستشفى الزاوية التعليمي. أجريت دراسة بأثر رجعي من 1 يناير 2022 إلى 31 ديسمبر 2022 في مستشفى الزاوية التعليمي. تم تضمين المرضى من جميع الأعمار وكلا الجنسين في الدراسة. تم تضمين التقارير المعملية للمرضى الذين لديهم مزرعة بول إيجابية (≥105 CFU / mL) واختبار حساسية المضادات الحيوية في الدراسة. من بين 1966 عينة، كانت 506 حالة مزرعة إيجابية. من بينهم 378 (74.70٪) من الإناث و 128 (25.30٪) من الذكور. تم تسجيل غالبية الثقافات الإيجابية في الفئة العمرية للمراهقين من 11 إلى 20 عامًا (38.14٪). فيما يتعلق بمسببات الأمراض البولية المعزولة، كانت الإشريكية القولونية هي العزلة البكتيرية السائدة بنسبة 261 (51.58٪) من إجمالي العينات. من ناحية أخرى، سجلت البكتيريا إيجابية الجرام (Staphylococcus spp) أقل مسببات الأمراض البولية وفرة بنسبة 15 (2.96٪) من إجمالي العينات المفحوصة. كانت Pseudomonas spp هي البكتيريا الأكثر مقاومة. بالنسبة لجميع البكتيريا سلبية الجرام كانت شديدة المقاومة لأوجمنتين، في حين كانت البكتيريا إيجابية الجرام شديدة المقاومة للبنسلين. أكدت النتائج التي تم الحصول عليها على ظهور بكتيريا شديدة المقاومة لمعظم مضادات الميكروبات المختبرة وتقترح الحاجة إلى قيام الأطباء بتغيير نمط علاجهم اعتمادًا على نتائج حساسية مضادات الميكروبات